Pixel-super-resolved lens-free quantitative phase microscopy with partially coherent illumination - Yang Chen; Xuejuan Wu; Linpeng Lu; Jiasong Sun; Runnan Zhang; Wenhui Lin; Yufan Chen; Maciej Trusiak; Peng Gao; Chao Zuo (npj Nanophotonics)
Abstract Lens-free on-chip microscopy (LFOCM) has been widely utilized in digital pathology, drug screening, point-of-care testing (POCT), and quantitative phase imaging (QPI) due to its high throughput imaging capability and compactness. Initially, coherent laser sources were used in LFOCM to generate interference fringes to reconstruct the intensity and phase information of an object. The use of partially coherent light-emitting diodes (LEDs) in LFOCM offers a more portable and cost-effective alternative to conventional coherent illumination sources. However, the coherence-gating effect from a relatively low degree of coherence may cause a blur of high-frequency information in holograms, leading to an inaccurate object recovery. Thus, we present a pixel-super-resolved lens-free quantitative phase microscopy (PSR-LFQPM) with partially coherent illumination, which not only compensates for the impact of low coherence without increasing the volume of the system but also suppresses the theoretical Nyquist-Shannon sampling resolution limit imposed by the sensor pixel size (0.9 μm). Based on the partially coherent imaging model, we integrate the spatial coherence transfer function (SCTF) obtained from the pre-calibrated LED source distribution during the iteration process to obtain an accurate high-resolution recovery. Applying PSR-LFQPM to image living HeLa cells in vitro, we achieve real-time dynamic high-throughput QPI performance (half-pitch resolution of 780 nm with a 1.41-fold improvement compared to results without considering the effect of coherence) across a wide FOV (19.53 mm2). The proposed method provides a compact, low-cost, and high-throughput lens-free on-chip microscopy system for biomedical and POCT applications.